Diseño de un sistema a través del método de costeo ABC para la hostería El Surillal en el área de cocina, ubicada en el cantón Salcedo en el sector del valle de Yanayacu en el período 2019. - Alvarez Salazar, Bertha Cecilia (2020)
The research project is a proposal of a system through the ABC method for the Hosteria el Surillal as an accounting tool that allows the owners to make decisions focused on optimizing the resources of products elaboration process. For this reason, it is vital that Surillal hostelry has a system that helps to verify the cost about the products elaboration and thus achieve accurate information to determine the activities in food preparation in the kitchen area, especially in the five best-selling dishes that have been taken for research , identification of resources needed and know real costs to be distributed to each products. Therefore, it is feasible to work with the ABC costing method in order to management can take decisions that help the economy growth and good performance service inside the hostelry. To achieve this objective, documentary and bibliographic compilation methods were used, as well as techniques such as personal interviews and observation file. It was applied to the chef who is the kitchen department boss. The file had open questions and it was useful to obtain information that will help to execute the design of the system mentioned above and to provide a solution to the lack of knowledge about the use of raw materials, work force and CIF. At the end of the research project, it was determined that the price obtained in each saled dish covers the resources costs used for their preparation, the workforce and the indirect costs which are involved in this area where its current prices are set by market competition and its real cost does not go over than the normal at the moment to be saled to the consumers. It is proposed to keep its current sale price because it generates a great profit of $ 6,07 which is equivalent to the 111,79% in “ la trucha el Surillal”, $ 1,06 which is equals to the 43,44% in potatoes with chicken, $4.17$4,17, the 71,53% in breaded shrimp, $ 1,93 which means the 34,65% in breated meat and $ 4,95 equals to 98,02% in grilled chop. According to the results obtained, there was a considerable gain profit.